Early Neurodevelopmental Outcome of Asphyxiated Newborns Treated with Therapeutic Hypothermia: A Non Randomised Cohort Study - Jyoti Prajapati; Devraj Singh; Pramila Ramawat; Nilesh Jain (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Therapeutic Hypothermia (TH) is now a proven model of treatment to prevent complications in asphyxiated newborns. Perinatal asphyxia is the leading cause of mortality and disability in India and developing countries. The TH is still not the standard treatment protocol in developing India, and data regarding early neurological outcomes after TH is lacking. Aim: To evaluate the early neurological outcome at 3, 6, and 9 months of asphyxiated newborns who received TH compared to non recipients. Materials and Methods: This was a non randomised cohort study conducted at the tertiary care teaching hospital. A total of 190 asphyxiated newborns admitted to Neonatal Intensive Care Unit (NICU) within 24 hours of life, meeting the laboratory and/ or clinical criteria of perinatal asphyxia were enrolled. Eligible newborns admitted within 6 hours of birth receiving TH were labelled as recipients, and those who received standard care were labelled as non-recipients. Neonates were assessed at 3, 6, and 9 months and compared for neurodevelopment using the Hammersmith Infant Neurological Examination (HINE) optimality score and Denver Developmental Screening Test II. Both groups were compared using t-test and chi-square test. Results: Out of the total 190 enrolled participants, 14 were excluded and 176 newborns were further divided into recipients and non recipients groups. Baseline demographic characters were similar in both groups. Seventy-five recipients were followed up till three months, 72 at six months, and 69 at nine months vs 62, 60, and 56 non recipients, respectively. Lesser number of recipients scored suboptimal scores (HINE score <67) at 3 months vs non recipients (20% vs 35.4%, mean/ SD 63 [3.43] vs 57 [4.55], [p<0.001]). At six months (HINE score<70), the incidence was 18% vs 21% (p=0.02), mean score 67 vs 61 (p<0.0001); and at 9 months (HINE score<73) the incidence was 14.4% vs 30.3% (p=0.048), mean score 72 vs 65 among recipient vs non recipients (p<0.0001). Recipients also had less incidence of severe disability (HINE score< 40) at 6 (8.3%vs 21.6% p<0.02), and 9 months (8.3% vs. 19.6%, p<0.04) as compared to non recipients. More recipients had a normal developmental screening at 3,6, and 9 months on the DDST scale. Recipients required fewer anti-epileptics at 3 and 6 months (3 vs 11) as compared to non recipients (p<0.05). Mortality was also less in recipients (7.8% vs 20.9%, p<0.05) as compared to non recipients. Conclusion: There was a significant developmental and neurological improvement with decreased mortality, less episode of seizures, reduction in the need for antiepileptic among recipients of TH compared to non recipients at 3, 6, and 9 months of age.